Pengembangan Media Berbasis Aplikasi Kodular dalam Pembelajaran Teks Persuasi di SMP Kelas VIII - Hermanto; Djuredje, Rizka A Hi; Himawan, Riswanda (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
Based on the results of the needs analysis at MTs Muhammadiyah Karangkajen Yogyakarta and SMP Negeri 11 Yogyakarta, it can be reflected that the use of learning media, especially persuasive text materials using application-based media, has yet to be maximized. Therefore, developing learning media based on the Kodular application is hoped to be a solution to learning persuasive text material. This study aims to; (1) describe the stages of Kodular application media in learning persuasion text material for class VIII SMP/MTs students; (2) describe the implementation of Kodular application media in learning persuasive text material in class VIII SMP/MTs students; and (3) describe Kodular application media's feasibility in learning persuasion text material for class VIII SMP/MTs students. The type of research used was R&D (Research and Development) using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The subjects of this study were students and expert validators. Meanwhile, the object of this research is media based on Kodular application in teaching persuasion text to class VIII SMP/MTs students. Data collection techniques used in this study were in the form of observation, interviews, and questionnaires. The data analysis technique used in this study uses quantitative-descriptive analysis, which can present data from the validation test results from experts in the form of numbers and describe the stages in developing learning media based on Kodular applications. The results of this study indicate that the Kodular application-based media that contains persuasive text material is